Over the Atlantic : Diplomacy and Paradiplomacy in EU and Latin America. - Astroza Suarez, Paulina. (Euroclio Series, 2023)
The book analyses diplomacy and paradiplomacy in the European Union and in Latin America from a multidisciplinary perspective. The paradiplomacy, as a means of unofficial relationships that reacts differently to the pressure of the international system, despite its relevance and importance, is scarcely analysed by academia.